PERANCANGAN FURNITUR PERKANTORAN (PROSES DESAIN, MANUFAKTUR, DISTRIBUSI, DAN KONSUMSI) - Wardani, Laksmi Kusuma (Dimensi Interior, 2010)
A furniture design of good quality has esoteric value, consisting of complexity of values in both knowledge and skill techniques as well as philosophical contents and methodological contents. The planning consideration of office furniture is designed with the concept of mobility that can be set or adjusted to the aim of increasing productivity, creativity, interaction, spontaneity, aesthetics, movement comfort and the ease of fixing, keeping, cleaning, as well the comfort in size, form, proportion and flexibility. The design should always undergo the processes of design, manufacturing, circulation, and distribution to produce a design of good quality.